Comparison study on common and recurrent sport injuries in upper and lower limb among volleyball players and ways of prevention - Jameel, Israa (Journal of Physical Education, 2015)
The research included five chapters: Chapter One: This chapter consisted of the introduction of the study and its importance. A brief description has been presented showing the level of senior students in Physical Education College and the common recurrent injuries in the upper and lower limb, reasons behind, and ways to prevent in volleyball. The importance of the study lied in classifying these sport injuries, identifying their time and the number of the students injured throughout the year. The problem of the study focused on the increasing number and frequency of the upper and lower limb injuries which lead to a low level of performance as well as the weakness and lack of information needed to help the player and the coach in avoiding the injury and how to prevent it. This chapter also included the fields of study: human, duration and place. Chapter two: This chapter tackled the theoretical and similar studies related to sport injuries. Axes of the study have distinctively showed the importance of sport injuries, how they occur, their causes, and occurring time in the body of a volleyball player. Chapter three: This chapter included the method of research. The researcher has used the descriptive method in survey approach on the subjects. It also included the means used, the data collected, and the pilot study previously applied using the form as well as the application of statistical means to treat the data. Chapter four:In this chapter results were displayed and scientifically analyzed and discussed basing on the collected data. The results showed significant differences in the rate of sport injuries when comparing. Chapter five: In this chapter the researcher came out with several recommendations such as: giving more attention to the general and special warming in the beginning of the class or throughout the year; taking care of the treatment of the injury completely when they occur; safety and security precaution should be taken when practicing any sport activity; setting correct training program in treatment and rehabilitation that limit the incidence of injury and the methods of prevention according to the data and scientific bases information